293 Primary Carcinoid Tumor in a Horseshoe Kidney: A Case Report. (11th January 2018) - Khatami, Rokhsareh; Liu, Jingxuan; Teodosescu, Andrei; Waltzer, Wayne
Abstract: Objectives: Renal carcinoid tumors are exceedingly rare tumors that have been primarily documented as case reports in the literature. Fifty years after the first report of a renal carcinoid, the prognosis and clinical behavior of these tumors remain unclear due to the rarity of these lesions. They seem to be more indolent than renal cell carcinoma (RCC), although metastases to regional lymph node, liver, and bone have been described; however, even with metastases, the survival rate is better than RCC. Methods: Here we present a 42-year-old woman with past medical history of hypertension and horseshoe kidney who presents for evaluation of renal mass on horseshoe kidney. She was previously followed for a cyst at the isthmus of the horseshoe kidney with CT scans; however, the lesion remained stable, and no further follow-up was obtained on the lesion after 2006. During recent work-up for elevated LFTs, the patient underwent a CT scan showing a 7.8 x 6.8 x 6.7 cm lobulated heterogeneous mass arising from the midline bridging cortical tissue. There is also an enlarged retroperitoneal lymph node suspicious for metastases in post-op CT scan. Results: The patient underwent partial nephrectomy. The gross specimen was a 10 x 7.5 x 6 cm encapsulated mass. Cut section showed yellow, hemorrhagic mass with solid and cystic structure. The H&E slides showed tightly packed cord and trabeculae of neoplastic cell, imparting a ribbonlike appearance. There were also some areas of solid growth with nest formation, calcification, and focal ossification. The immunohistochemistry shows tumor cells were positive for CAM5.2, synaptophysin, chromogranin, and NSE, and negative for AE1/AE3, PAX8, S100, SMA, CD31, WT-1, CK7, and CK20. Conclusion: It is important to have keen knowledge of this rare entity and use appropriate immunohistochemical staining for neuroendocrine markers. Since carcinoid tumors are considered low-grade malignant tumors, correct histological diagnosis helps to avoid unnecessary aggressive treatment.